2011
DOI: 10.1007/s10692-011-9313-4
|View full text |Cite
|
Sign up to set email alerts
|

Medical hydrogels based on bioactive compounds. Synthesis, properties, and possible application for preparing bactericidal materials

Abstract: Several physicochemical analytical methods were used to study aqueous solutions and hydrogels based on L-cysteine and silver nitrate. It was found that anions played a decisive role in forming the threedimensional gel-network in dilute silver-cysteine solutions. The ability to use silver-cysteine solutions and hydrogels to prepare bactericidal fi bers and fabrics was examined.Self-assembly of supramolecular structures in solutions has recently attracted increased worldwide interest. This timely problem compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 4 publications
0
8
0
5
Order By: Relevance
“…Several comprehensive reviews have focused on this subject. 1066 , 1067 In the following section, we only give a brief discussion of the works on antibacterial hydrogelators reported over the past decade.…”
Section: Applicationsmentioning
confidence: 99%
“…Several comprehensive reviews have focused on this subject. 1066 , 1067 In the following section, we only give a brief discussion of the works on antibacterial hydrogelators reported over the past decade.…”
Section: Applicationsmentioning
confidence: 99%
“…Polylysine, a popular AMP reported by Zhou et al, has been applied in photopolymerized antibacterial hydrogels, which generated promising coatings for medical devices and implants . In addition to antibacterial peptide maximin‐4‐loaded PHEMA hydrogels, l ‐cysteine‐ and silver nitrate (AgNO 3 )‐loaded hydrogels were proved to possess antibacterial activity against Staphylococci , Bacilli , Escherichia , and P. aeruginosa strains …”
Section: Hydrogels With Inherent Antibacterial Activitymentioning
confidence: 99%
“…AMP maximin-4-loaded poly (2-hydroxyethyl methacrylate) hydrogels, 244 l-cysteine-and silver nitrate-loaded hydrogels were proved to have qualified antibacterial activity. 245 Although AMPs still have disadvantages, such as tissue toxicity and hemolysis, 246,247 they also exhibited a higher antimicrobial biocompatibility index value compared with synthetic drugs with similar structures, 248,249 and a lot of studies have attempted to improve the biocompatibility. [234][235][236] A cell adhesive polypeptide and PEG hydrogel with inherent antibacterial activity was developed by Song et al as a potential scaffold for cutaneous wound healing.…”
Section: Antimicrobial Polypeptidesmentioning
confidence: 99%
“…286 Some researchers synthesized antimicrobial Ag NPs and impregnated them into antifouling zwitterionic hydrogels, thus getting mussel-inspired, antifouling, antibacterial hydrogels with great potential in wound healing applications (Figure 8). 287 Both bactericidal hydrogels based on l-cysteine and silver nitrate and Ag(I)-glutathione hydrogel which exhibited improved cytocompatibility were reported in 2011, 245,288 offering more possibilities on potential application in biomedical field such as burn wound dressings. For other combinations, Ag NP-curcumin composite hydrogels demonstrated that incorporation of curcumin into these hydrogel nanocomposites would further enhance their antibacterial efficacy.…”
Section: Synergistic Effective Hydrogels Containing Metal Nanoparticlesmentioning
confidence: 99%